Identification of Dinaciclib and Ganetespib as anti-inflammatory drugs using a novel HTP screening assay that targets IFNγ-dependent PD-L1 - Hagbi-Levi, Shira; Abraham, Michal; Gamaev, Lika; Mishaelian, Inbal; Hay, Ophir; Zorde-Khevalevsky, Elina; Wald, Ori; Wald, Hanna; Olam, Devorah; Weiss, Lola; Peled, Amnon (Frontiers in Immunology, 2025)
IntroductionIFNγ plays both positive and negative roles in the regulation of innate and adaptive immune responses against tumors and virally infected tissues by upregulating CXCL10 and PD-L1 expression.MethodsTo identify novel pathways and drugs that regulate the IFNγ-dependent PD-L1, we expressed GFP under the control of mouse PD-L1 promoter in mouse cancer cells that up regulate PD-L1 and CXCL10 in response to IFNγ stimulation. Using these cells, we screened an FDA approved library of 1496 small molecules known for their ability to inhibit IFNγ-dependent increase in PD-L1.ResultsWe identified 46 drugs that up regulated and 4 that down regulated IFNγ-dependent PD-L1 expression. We discovered that in addition to the known JAK inhibitors Ruxolitinib and Baricitinib, Dinaciclib, a CDK1/2/5/9 inhibitor, and Ganetespib, a Hsp90 inhibitor, significantly inhibit both PD-L1 and CXCL10 expression in the model cells. Furthermore, both drugs suppressed IFNγ-dependent CXCL10 and PD-L1 expression in-vitro in primary human lung cells and human cancer cells. These drugs also significantly inhibited delayed-type hypersensitivity (DTH) in-vivo in an inflammation mouse model.DiscussionOur novel screening platform can therefore be used in the future to identify novel immunomodulators and pathways in cancer and inflammation, expanding therapeutic horizons.